Continuity or change? Red-Green social policy after 16 years of Christian-Democratic rule - Martin Seeleib-Kaiser (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2003)
The 'parties matter theory' in welfare state research argues that it makes a differences whether liberal (conservative), christian - democratic or social - democratic parties are in power, since they pursue different social policies. Hence, we would expect specific policy changes after a change in government. This theory constitutes the starting point for an analysis of the Red?Green social policies during the past four years. First, the paper briefly scrutinizes the social policy priorities and policies during the long rule of the Christian Democratic-Liberal coalition against the backdrop of the normative and institutional foundations of the German welfare state in the golden post-World War II era. In a second step, the social policy priorities and aims of the Social Democrats and Greens are scrutinized in greater detail. The analysis in the main section of the paper focuses on the main social policy changes legislated during the past four years in the various domains of the welfare state. A comparison of the policies of the previous government with the programmatic aims as well as the legislated policies of the Red-Green government leads to the conclusion of policy continuation. However, policy continuation should not be mistaken with policy stalemate. Moreover, the Red-Green government continues to pursue reforms in the policy direction already followed by the previous government. Accordingly, the 'parties matter theory' cannot sufficiently explain the more recent social policy development in the Federal Republic of Germany. – – Nach der Parteiendifferenztheorie in der Wohlfahrtsstaatsforschung macht es einen Unterschied hinsichtlich der spezifischen Gestalt von Sozialpolitik, ob liberale (konservative), christdemokratische oder sozialdemokratische Parteien an der Macht sind. Entsprechend wäre nach einem politischen Machtwechsel ebenso ein Politikwechsel zu erwarten. Diese Theorie dient dem Arbeitspapier als Ausgangspunkt für die Analyse der rot-grünen Sozialpolitik der vergangenen vier Jahre. In einem ersten Schritt werden die sozialpolitischen Prioritäten sowie Politiken während der langen Herrschaft der christlich-liberalen Koalition vor dem Hintergrund der normativen und institutionellen Fundamente des deutschen Wohlfahrtsstaates in der Nachkriegszeit kurz skizziert, bevor in einem zweiten Schritt auf die sozialpolitische Programmatik der Sozialdemokratie sowie der Grünen eingegangen wird. Der Hauptteil der Analyse widmet sich den zentralen sozialpolitischen Gesetzesänderungen in den vergangenen vier Jahren. Ein Vergleich der Politiken der Regierung Kohl mit den sozialpolitischen Zielen sowie den bereits verabschiedeten Gesetzesmaßnahmen von Rot-Grün führt schließlich zu dem Ergebnis der Politikkontinuität. Jedoch darf Politikkontinuität nicht mißverstanden werden mit Politikstillstand. Vielmehr verfolgt die rot-grüne Koalition die von der Vorgängerregierung eingeschlagene Reformrichtung weiter. Insoweit kann die Parteiendifferenztheorie nicht hinreichend die jüngsten sozialpolitischen Entwicklungen in der Bundesrepublik Deutschland erklären.
Keywords: 300